2014
DOI: 10.1108/bfj-02-2013-0042
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative information processing of nutrition facts panels

Abstract: Purpose – Quantitative information on nutrition labels (nutrition facts panels (NFPs)) is often conveyed in the form of absolute weights (i.e. milligrams or grams) and reference values (i.e. per cent daily values (%DVs)) which provide information regarding nutrient levels within the context of a total daily diet. Some evidence suggests that %DVs are preferred over the weights and may be better at communicating nutrition information. However, age differences are often neglected in past work, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 48 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Previous research from Health Canada suggests that Canadians struggle with using the %DV to compare across food products to choose healthier products, and only around half of consumers report looking at the %DV information when purchasing products . Conversely, recent eye‐tracking research found that consumers who pay more attention to the %DV values are better able to evaluate the healthfulness of food products . Although the inclusion of a %DV for sugars is not perfect, it does provide some context for consumers.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research from Health Canada suggests that Canadians struggle with using the %DV to compare across food products to choose healthier products, and only around half of consumers report looking at the %DV information when purchasing products . Conversely, recent eye‐tracking research found that consumers who pay more attention to the %DV values are better able to evaluate the healthfulness of food products . Although the inclusion of a %DV for sugars is not perfect, it does provide some context for consumers.…”
Section: Discussionmentioning
confidence: 97%